Functions of Narrative Genres for Lived Religion - Tuija, Hovi (Donner Institute, 2018)
he article presents the object and results of a study which combines the psychology of religion and folkloristics in the form of a qualitative analysis of empirical ethnographic material compiled from sources in a local neo-charismatic congregation called the ‘Word of Life’. Personal narrative is discussed as a genre which represents the collective tradition of a religious community. It is a socially-learned speech act and a means of interpreting and sharing religious experience, thus constructing and confirming the faith of the community, both individually and collectively. In the neo-charismatic tradition, everyday speech draws on a literal (biblical) tradition as well as on socially-shared narrative genres such as ritual testimonies, prophecies, sermons and casual, personal narratives of co-believers. The faith-creative power of these stories can be found in their performative utterances and evaluative structures as well as in non-communication.